(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article is devoted to the issues of transposition of language units, in particular morphological transposition. The main approaches to the interpretation of transposition, revealing various aspects of this phenomenon, are considered. Morphological transposition is presented taking into account the differences between systemic (primary) and non-systemic (secondary) meanings of morphological categories as a consequence of the figurative or neutralized use of the grammatical form. The variation of grammatical forms at the level of connotations is shown, leading to the functional specialization of the grammatical form in this type of usage.